1985
DOI: 10.3354/meps023015
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term influences of the immigration of postlarval banana prawns Penaeus merguiensis, into a mangrove estuary of the Gulf of Carpentaria, Australia

Abstract: Postlarval Penaeus merguiensis de Man were sampled regularly at the mouth of the Norman River estuary in the south-eastern Gulf of Carpentaria, Australia. from 1975 to 1979. A grid of stations up to 10 km offshore from the estuary mouth was also occupied over a 24 h period during November 1978. In these offshore stations, postlarvae migrated vertically in the water column in response to changes in tidal height, rising to near the surface just before low tide. Postlarvae entered the estuary throughout the flood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The natural estuarine habitats provide nurseries for many commercially important species, including prawns, crabs, fish and sharks [17], [18], [19], and are ecologically important to various stages in the lifecycle of sharks (e.g. [20], [21], [11]).…”
Section: Introductionmentioning
confidence: 99%
“…The natural estuarine habitats provide nurseries for many commercially important species, including prawns, crabs, fish and sharks [17], [18], [19], and are ecologically important to various stages in the lifecycle of sharks (e.g. [20], [21], [11]).…”
Section: Introductionmentioning
confidence: 99%
“…the Pearl River estuary. Moreover, heavy rainfall during the summer months exaggerates the salinity gradient and may enhance the immigration of larvae into the estuarine nursery areas (Staples & Vance, 1985). Excessive rainfall may, however, reduce the area of a salinity regime suitable for successful settlement and growth of penaeid larvae (Barrett & Ralph, 1976;Garcia & Le Reste, 1981).…”
Section: Larval Occurrence and Recruitmentmentioning
confidence: 99%
“…Several studies have shown evidence that penaeid post-larvae migrate vertically as a means to enhance recruitment to estuaries (Staples & Vance, 1985;Forbes & Benfield, 1986;Dall et al, 1990). Tidally based endogenous rhythms with peaks of movement around flood tide have been found for several species (Copeland & Truitt, 1966;Garcia & Le Reste, 1981;Mair et al, 1982;Forbes & Benfield, 1986).…”
Section: Introductionmentioning
confidence: 99%